THE POTENTIAL OF TEACHING VIETNAMESE IN INDONESIA UNDER A COMPREHENSIVE STRATEGIC PARTNERSHIP BETWEEN VIETNAM AND INDONESIA - Minh Tri Nguyen; Indra Sarathan (Intermestic: Journal of International Studies, 2026)
This article examines the potential development of Teaching Vietnamese to Speakers of Other Languages (TVSOL) in Indonesia within the framework of the Vietnam–Indonesia Comprehensive Strategic Partnership (CSP). The study aims to analyze the geopolitical, economic, and educational factors driving the need for Vietnamese language education in Indonesia, while also identifying institutional and pedagogical challenges in establishing such programs. The research employs theories of second language acquisition, negative language transfer, human capital theory, and soft power diplomacy to explain both linguistic difficulties and the strategic significance of language education. Using a qualitative research design, the study employs documentary research, a systematic literature review, and qualitative content analysis of policy documents, labor market data, academic literature, and online educational platforms. The findings reveal that increasing bilateral cooperation in trade, tourism, investment, and education has generated growing demand for Vietnamese language proficiency in Indonesia, particularly in business, diplomacy, and cross-cultural communication sectors. However, the absence of formal Vietnamese language programs, limited institutional support, and significant phonological differences between Indonesian and Vietnamese remain major barriers. The study concludes that integrating Vietnamese language education into the CSP agenda through government support, university partnerships, teacher training, and public–private collaboration could strengthen Indonesia’s regional engagement with Vietnam and contribute to broader ASEAN cooperation.